Toxicity Of Diclofenac Sodium In Broiler Birds - Sharma, R. K.; Shrman, K.; Sharma, Varsha; Bhamre , N.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
The present research work was conducted to study the effect of diclofenac sodium on broilers birds. The study was carried out on 40 broiler birds equally divided in two group i. e. treatment and control. In treatment group diclofenac sodium was administered @5mg/kg b.w. /day for 21 days. In treatment group mortality, reduction in weight gain and lameness was observed. However, except haemoglobin and heterophil count, most of other haematological parameters did not show any significant changes. Significantly higher levels of uric acid, creatinine and urea were found in treatment group, denoting renal damage. Necropsy examination of dead bird show deposition of uric acid crystals on internal organs.
Keywords: Diclofenac sodium; gout; broiler bird; uric acid crystal; nephrotoxicity